“Olaegbékizomba” festas, dramaturgias e Teatros Negros na cidade de São Paulo - Nascimento, Jéssica Gomes do (2022)
Starting from the collective gesture and the personal step, this master’s thesis inquires memories, confluences, and insurgencies of the black theaters in São Paulo. The research captures the dramaturgical imagination as a source to tell paths that were mobilized by art for coexistence in the common such a common space. The thesis comments on memories and poetic insurgencies of Cia Negra de Revistas (1926 - 1927), Teatro do Sentenciado (1942 - 1944), Teatro Experimental do Negro Paulista (1944 - 1965), CECAN (1972 - 1974), Capulanas Cia de Arte Negra (2013) and Carcaça de Poéticas Negras (2017). In addition, it recalls the work of actors and actresses such as: De Chocolat, Augusto Stuart, Armando Valdomiro, Abdias do Nascimento, Geraldo Campos de Oliveira, Tereza Santos, Eduardo de Oliveira e Oliveira, Cidinha da Silva and Jonny Salaberg. Despite the disadvantages and inequalities to which black peoples were subjected throughout history, they – more precisely, black artists working in the city of São Paulo in the 20th and 21th centuries – created an intense network of articulation inside and outside the country. This articulation constitutes what we call the Afrocorrespondence relationship